(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to identify the role of information technology improving the quality of services banking for Libyan commercial banks. To achieve the objective of the study therefore. It depended on the descriptive analytical approach, one main hypothesis was formulated. And five sub- hypotheses were formulated. The number of banks participating in the study five commercial banks. The study relied on the questionnaire as a tool for collecting the necessary data. The results shown Analysis that there is a role for information technology in improving the quality of banking services Through the dimensions of (tangibility, reliability, responsiveness, security/trust, empathy) in Libyan commercial banks. The study recommended a set of recommended, the most important of which is the adoption by the senior management of the policy of spreading the culture of quality of banking services among all employees to know its principle and concept, by holding seminars, meeting and workshops. And providing documented and publications related to quality. Up to being convinced of it, to the point of full commitment on their part to implement it.